DEVELOPMENT OF FIBROUS CALCITE VEINS RELATED TO HYDROCARBON GENERATION AND OVERPRESSURING IN ORGANIC‐RICH SHALE SOURCE ROCKS: THE VACA MUERTA FORMATION, NEUQUÉN BASIN, ARGENTINA. (24th March 2022) - Spacapan, J. B.; Comerio, M.; Ruiz, R.; Rocha, E.
Abstract : Fibrous calcite bed‐parallel veins (BPVs) are a typical feature of the Upper Jurassic – Lower Cretaceous Vaca Muerta Formation in the subsurface of the Neuquén Basin (Argentina). The formation is considered to be the main source rock in the basin as well as an important unconventional play. This study examines the growth of BPVs through an analysis of core from three wells located along a transect extending for some 150 km from the NE Platform near the basin margin in the east to the Agrio fold‐and‐thrust belt at the Andean deformation front in the west. The main objective is to integrate fluid inclusion data with the palaeothermal and palaeopresure evolution obtained from a regional‐scale 2D basin and petroleum systems model to examine the timing of fracture development and its relationship with hydrocarbon generation in the Vaca Muerta Formation through time. The apertures of BPVs were measured in more than 360 m of core from three wells (wells A, D and E). This data was combined with optical petrography to investigate the number of calcite cementation events, and the temperature of cement precipitation based on fluid inclusion data. The organic geochemical and mineralogical characteristics of the Vaca Muerta source rock were also analysed. The integrated results were incorporated into a poro‐elastic basin model to investigate the impact of horizontal shortening due to Andean compression on pore pressure development and fracturing in the Vaca Muerta Formation. This framework allowed the timing of BPV formation to be determined together with possible mechanisms governing overpressure conditions through time. Near the Andean deformation front in the west of the modelled section where the Vaca Muerta Formation is in the wet gas window (well D) and dry gas window (well A), BPVs are characterized by two or more generations of calcite fibres indicating multiple growth phases. Calcite which precipitated during cementation event 1 (E1) in the internal zones of BPVs consists of crystals oriented perpendicular to fracture walls, indicating perpendicular vein opening. Calcite precipitated during cementation event 2 (E2) in the outer zones of BPVs includes curved and oblique crystals. During this phase, shear occurred between the opening vein walls as a result of horizontal shortening. Cementation event 3 (E3) is characterized by an equant mosaic of calcite crystals which preserve intracrystalline porosity. E1cements formed between 110 and 90 Ma with trapping temperatures of ∼112 °C (upper Vaca Muerta, well A) and ∼125 °C (lower Vaca Muerta, well D). Fracturing resulted from disequilibrium compaction and from volumetric expansion due to primary cracking of kerogen within the oil window. E2 cements record a trapping temperature of ∼159 °C and formed between 70 and 55 Ma (lower Vaca Muerta, well D) during maximum burial of the Vaca Muerta Formation, synchronous with the secondary cracking of retained liquid hydrocarbons and the beginning of Andean compression. E3 cements (upper Vaca Muerta, well A) have a trapping temperature of ∼162 °C, and formed between 65 Ma and 53 Ma synchronous with the generation of thermogenic gas. By contrast, in the east of the modelled section in the less deformed foreland area of the Neuquén Basin where the Vaca Muerta Formation is in the early oil window (well E), BPVs are composed of a single generation of calcite fibres (E1)with a trapping temperature of ∼118 °C. The E1 cement is characterized by calcite crystals which are oriented perpendicular to fracture walls with no evidence of shearing. According to model simulations, cementation here occurred between 64 Ma and 53 Ma during maximum burial and was related to overpressures which resulted from both disequilibrium compaction and primary transformation of kerogen into oil. The data presented suggests that in some intervals of the Vaca Muerta Formation, a slight increase in TOC content is accompanied by an increase in vein thickness, with the highest number of cementation events occurring towards the Andean deformation front in the west of the study area compared to the foreland in the east.